Pengaruh E-Wom, Kepercayaan, Kemudahan Penggunaan Terhadap Keputusan Pembelian Pada Bukalapak Di Kota Batam - Walina Yenita Br Siahaan; Hikmah, Hikmah (SCIENTIA JOURNAL, 2025)
In the increasingly advanced digital era, the development of information and communication technology has changed the way consumers make decisions to buy products. E-commerce platforms such as Bukalapak are now the main choice for shopping. The purpose of this study was to examine the extent to which E-WOM, trust, and ease of use influence purchasing decisions on Bukalapak in Batam City. This study uses a quantitative approach with a descriptive method, involving respondents who are Bukalapak users in Batam City in 2024. Because the population size is not known for certain, the sample was taken using the Jacob Cohen formula, resulting in 204 respondents selected using a purposive sampling technique. The data obtained were analyzed using data quality tests, classical assumption tests, and influence tests and hypothesis tests. The results of the t-test, E-WOM is proven to have a positive and significant partial influence on purchasing decisions, trust is proven to have a positive and significant partial influence on purchasing decisions, ease of use is proven to have a positive and significant partial influence on purchasing decisions. The results of the F test show that E-WOM, trust, and ease of use also have a positive and significant simultaneous influence on purchasing decisions.